Adsorption of Rhodamine B by Palm Kernel Shell Adsorbents - Yong, Q.Z.; A. Zaini, M.A (Journal of Engineering and Technology (JET), 2016)
This study was aimed at evaluating the adsorptive removal of rhodamine B dye (RhB) by palm kernel shell adsorbents. The precursor was mixed with potassium hydroxide solution, and the mixture was further heated using furnace (FC) and microwave (MC). Microwave-assisted water (steam) treatment (MH) of palm kernel shell char was also performed for comparison. The adsorbents were characterized according to the specific surface area, surface morphology and surface functional groups. Result indicates that the RhB removal by adsorbent is in the order: MC>FC>MH, that is in agreement with the surface chemistry of the adsorbents. The adsorption of RhB by palm kernel shell adsorbents agreed well with the Redlich-Peterson model, suggesting the monolayer coverage on the heterogeneous surface. Kinetics study demonstrates that MC obeyed the pseudo-first-order model, and signifies that the external diffusion to overcome the adsorbent mass transfer resistance as the rate-determining step.